Integrability and Dynamics of Quadratic Three-Dimensional Differential Systems Having an Invariant Paraboloid - Messias, Marcelo [UNESP]; Reinol, Alisson C. [UNESP] (World Scientific Publishing, 2016)
Invariant algebraic surfaces are commonly observed in differential systems arising in mathematical modeling of natural phenomena. In this paper, we study the integrability and dynamics of quadratic polynomial differential systems defined in 3 having an elliptic paraboloid as an invariant algebraic surface. We obtain the normal form for these kind of systems and, by using the invariant paraboloid, we prove the existence of first integrals, exponential factors, Darboux invariants and inverse Jacobi multipliers, for suitable choices of parameter values. We characterize all the possible configurations of invariant parallels and invariant meridians on the invariant paraboloid and give necessary conditions for the invariant parallel to be a limit cycle and for the invariant meridian to have two orbits heteroclinic to a point at infinity. We also study the dynamics of a particular class of the quadratic polynomial differential systems having an invariant paraboloid, giving information about localization and local stability of finite singular points and, by using the Poincaré compactification, we study their dynamics on the Poincaré sphere (at infinity). Finally, we study the well-known Rabinovich system in the case of invariant paraboloids, performing a detailed study of its dynamics restricted to these invariant algebraic surfaces.
Keywords: Darboux theory of integrability; elliptic paraboloid; homoclinic and heteroclinic orbits; invariant algebraic surfaces; invariant parallels and meridians; Poincaré compactification; Polynomial differential systems; Rabinovich system